Restoring victims’ confidence: Victim-centred restorative practices - Wemmers, Jo-Anne M. (International review of victimology, 2023)
Victimization, and in particular sexual violence, undermines victims’ confidence and self-esteem. Victims often feel guilty and blame themselves for what happened. Fearing negative reactions, victims of sexual violence are often reluctant to report the crime to police. When victims do report to the police, the criminal justice process is often difficult and most sexual violence cases do not end in a conviction. Restorative practices (hereafter RP) have been presented both as a possible alternative and a complement to the criminal justice process, which could improve victims’ experiences. However, there is also considerable resistance to the use of RP in cases of gender-based violence. Using a victim-centred lens, in which it is seen as a reaction to victimization that aims to address the needs of the victim and allow them to advance in their healing process, we examine RP. Based on semi-structured interviews with 18 victims of sexual violence in Canada who participated in RP, we explore the healing potential for victims. We conclude that for victims of sexual violence, victim-centred RP should be viewed as a tool for victim support and not only as another tool in the criminal justice toolkit.